(untitled) (Swiss Medical Weekly, 2014)
OBJECTIVE: To evaluate the rates of penicillin, clindamycin and erythromycin resistance and the serotype distribution among isolates of group B streptococcus (GBS) obtained from pregnant women at the University Hospital of Bern in Switzerland. METHODS: We prospectively collected screening samples for GBS colonisation at the University Women’s Hospital Bern, Switzerland, between March 2009 and August 2010. We included 364 GBS isolates collected from vaginal, cervical or vaginal-perianal swabs at any gestation time. The minimal inhibitory concentrations for penicillin, clindamycin and erythromycin were established using Etest with 24 hours of incubation, and inducible clindamycin resistance was tested with double disk diffusion tests. Serotyping was done with a rapid latex agglutination test or, if not conclusive, with polymerase chain-reaction (PCR) testing. We looked for significant associations between resistance patterns, age groups, serotype and ethnicity. RESULTS: All isolates were susceptible to penicillin. Resistance rates were 14.5% for erythromycin and 8.2% for clindamycin. Of 364 isolates, 5.8% were susceptible to clindamycin but not to erythromycin, although demonstrating inducible clindamycin resistance. Hence, the final reported clindamycin resistance rate was 14%. Serotype III was the most frequent serotype (29%), followed by V (25%) and Ia (19%). Serotype V was associated with erythromycin resistance (p = 0.0007). In comparison with all other ethnicities, patients from Asia showed a higher proportion of erythromycin and clindamycin resistance (p = 0.018). No significant association between resistance patterns and age groups was found. CONCLUSION: In pregnant women with GBS colonisation, penicillin is the antibiotic of choice for intrapartum prophylaxis to prevent neonatal early-onset GBS sepsis. In women with penicillin allergy and at high risk for anaphylactic reaction, clindamycin may be an alternative. The resistance rate for clindamycin at our institution was 14%; therefore, susceptibility must be tested before administration.